2010
DOI: 10.4317/medoral.15.e531
|View full text |Cite
|
Sign up to set email alerts
|

A clinical longitudinal study 323 porcelain laminate veneers. Period of study from 3 to 11 years

Abstract: Objective: The objective of this study was to evaluate the clinical results of 323 porcelain laminate veneers over a period of 3 to 11 years. Material and Methods: This study included 70 patients, aged between 18 and 74 years. Of the 323 total veneers, 124 were of a simple design and 199 were of a functional design. The condition of the soft tissues and hygiene, in addition to the condition of the abutment teeth, the restorations and patient satisfaction were all clinically examined. In carrying out the statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
2
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 15 publications
4
56
2
7
Order By: Relevance
“…Smales and Etemadi (21) considered incisal coverage a protective factor; on the other hand, Granell-Ruiz et al (9) and Gürel et al (12) reported incisal coverage to be a risk factor for failures. Gürel et al (12) affirmed that the incisal coverage increased the chance of ceramic laminate veneer failure by 2.3 times.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Smales and Etemadi (21) considered incisal coverage a protective factor; on the other hand, Granell-Ruiz et al (9) and Gürel et al (12) reported incisal coverage to be a risk factor for failures. Gürel et al (12) affirmed that the incisal coverage increased the chance of ceramic laminate veneer failure by 2.3 times.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, incisal edge preparation was considered unnecessary to ensure or improve restoration strength, as this thin palatal extension tended to show more cracks. This occurred because the fracture lines propagated due to repeated heavy mechanical loading, that eventually led to a large porcelain fracture in this region (9,16,18). However, there was no consensus about the most indicated preparation design, with or without incisal coverage, and the type of palatal design (butt joint or palatal chamfer) (2, 3, 5-7, 9, 10, 12, 14-16, 18-21).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations